Answer:
-3x2 + 12x - 8
Step-by-step explanation:
Equation at the end of step 1
((0 - 3x2) + 12x) - 8
STEP
2
:
STEP
3
:
Pulling out like terms
3.1 Pull out like factors :
-3x2 + 12x - 8 = -1 • (3x2 - 12x + 8)
Trying to factor by splitting the middle term
3.2 Factoring 3x2 - 12x + 8
The first term is, 3x2 its coefficient is 3 .
The middle term is, -12x its coefficient is -12 .
The last term, "the constant", is +8
Step-1 : Multiply the coefficient of the first term by the constant 3 • 8 = 24
Step-2 : Find two factors of 24 whose sum equals the coefficient of the middle term, which is -12 .
-24 + -1 = -25
-12 + -2 = -14
-8 + -3 = -11
-6 + -4 = -10
-4 + -6 = -10
-3 + -8 = -11
-2 + -12 = -14
-1 + -24 = -25
1 + 24 = 25
2 + 12 = 14
3 + 8 = 11
4 + 6 = 10
6 + 4 = 10
8 + 3 = 11
12 + 2 = 14
24 + 1 = 25
15/24 because 5/3 X 1/4 = 5/12 X 3/2= 15/ 24
Given
0.24 × (number of 6th grade students) = 30
Find
(number of 6th grade students
Solution
Divide by 0.24.
... (number of 6th grade students) = 30/0.24 = 125
Answer:
3.5 in.
Step-by-step explanation:
17.5 ÷ 5 = 3.5
Step-by-step explanation:
R' = (-2,0)
E' = (-2,2)
F' = (4,4)